Dry eye status among UiTM Puncak Alam office workers using Ocular Surface Disease Index (OSDI) questionnaire / Anis Asyiekin Zainudin - Zainudin, Anis Asyiekin (2016)
Purpose: Increased risk of dry eye disease (DED) was reported to be a concern among office workers and could significantly give a major impact on their quality of life, especially work productivity. The objectives of this study were to determine the prevalence of dry eye disease according to the severity and to identify the differences of OSDI score between the groups of computer usage duration, age, and gender risk factors among UiTM Puncak Alam office workers. Method: In this current survey which conducted from February 2016 until April 2016, a total of 43 office workers (16 males and 27 females) were participated and completed the Ocular Surface Disease Index (OSDI) questionnaire in the time frame given via an electronic tool survey called Survey Monkey. Results: The mean OSDI score for the study population was 28.47±22.21 whereas the mean OSDI score according to the severity were 5.30±3.95 (normal), 18.33±1.95 (mild), 27.01±3.96 (moderate), and 54.64±12.86 (severe). Overall, 69.8% of the respondents were identified with DED (OSDI score ≥ 13). Males showed significantly higher mean OSDI score than females (p= 0.037). The prevalence of all dryness symptoms were markedly reported in < 25 years old age group (p=0.037) and longer computer usage duration of ≥ 5 hours per day. However, no significant difference between computer usage duration group was observed (p= 0.505). The most common reported DED symptom was sensitive to light and intense symptoms were markedly reported in the air-conditioned surrounding. Conclusion: The results showed that symptoms of dry eye were prevalent among office workers. Males and younger age were found to be linked with dry eye symptoms in office environment.